ANALISIS PERHITUNGAN, PEMUNGUTAN, DAN PELAPORAN PPH 21 PEGAWAI TETAP BERDASARKAN UU No 7 TAHUN 2021 PADA PT. BANK RAKYAT INDONESIA (Persero) KANTOR CABANG MANADO - Anggelina Warokka; Inggriani Elim; Steven Tangkuman (GOING CONCERN : JURNAL RISET AKUNTANSI, 2023)
This study aims to determine how the calculation, collection, and reporting of Pph 21 on Permanent Employees of PT Bank Rakyat Indonesia Manado Branch Office based on Law No. 7 Year 2021. This research uses descriptive qualitative research. With data collection sourced from secondary data, namely documentation from documents from the company and primary data which is the result of interviews with respondents. The results of this study indicate that PT Bank Rakyat Indonesia Manado Branch Office calculates Income Tax 21 using the latest rates based on Law No. 7 of 2021 with the With Holding system collection system, namely the company is responsible for collecting Income Tax 21 from permanent employees. However, it was found that there was still an error in the calculation of the determination of PKP, where there was a difference of one handred thousand rupiah, so that the amount of tax paid was overpaid.. For the timely reporting of Income Tax 21, PT. T. Bank Rakyat Indonesia Manado Branch Office is carried out on average on the 10th so that the reporting and depositing of SPT does not exceed the deadline.   Keywords : Calculation, Collection, Reporting, Income Tax 21, Permanent Employees